PLANT COMMUNITIES ON COASTAL DUNES IN LAZIO (ITALY) - STANISCI, A.; ACOSTA, A.; ERCOLE, S.; BLASI, C. (Annali di Botanica, 2004)
Aim of the paper is to describe the conservation state of the dune plant communities of Lazio (central Italy), using both original and already published phytosociological relevés. This case study in particular analyses the effects of human disturbance on the species composition and the vegetation zonation in coastal sandy landscape, already classified in three land facets. 13 plant associations were recognised and 9 of them were identified as potential natural vegetation types for the sandy coastal ecosystems of Lazio. Incidence of ruderal species and alien taxa were calculated for each plant community and for each land facet. The results have produced evidence that, even if Lazio coastline is largely occupied by human settlements or infrastructures, several sites still preserve an high plant communities diversity and few alien taxa inside the natural habitats occur. On the contrary where the human impact is intense, dune plant communities disappear or if they are still present, the vegetation zonation is incomplete, ruderals are abundant and alien species are locally common. A data-base of dune plant diversity was realised for a monitoring purpose.